2014
DOI: 10.1161/circulationaha.113.007106
|View full text |Cite
|
Sign up to set email alerts
|

Risk of End-Stage Renal Disease and Death After Cardiovascular Events in Chronic Kidney Disease

Abstract: Sunnybrook Health Sciences Center (SHSC) is a tertiary-care hospital affiliated with the University of Toronto which serves a diverse Background-Patients with chronic kidney disease stages 3 to 5 (glomerular filtration rate <60 mL/min/1.73m2 ) are at increased risk of cardiovascular (CV) disease when compared with patients with less severe chronic kidney disease. How CV events modify the subsequent risk of progression to end-stage-renal disease (ESRD) or all-cause mortality (ACM) before ESRD is not well known.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
43
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 38 publications
13
43
0
5
Order By: Relevance
“…21,22 Similarly, episodes of acute coronary syndrome or congestive heart failure may increase the risk of death and also, cause true GFR decline. 23,24 However, we observed similar associations of antecedent eGFR decline with non-CVD mortality as we did with CVD mortality (albeit in the limited cohorts with these data). Previous investigations have suggested that variability in the eGFR itself may be associated with higher ACM risk.…”
Section: Discussionsupporting
confidence: 83%
“…21,22 Similarly, episodes of acute coronary syndrome or congestive heart failure may increase the risk of death and also, cause true GFR decline. 23,24 However, we observed similar associations of antecedent eGFR decline with non-CVD mortality as we did with CVD mortality (albeit in the limited cohorts with these data). Previous investigations have suggested that variability in the eGFR itself may be associated with higher ACM risk.…”
Section: Discussionsupporting
confidence: 83%
“…Close monitoring and management of comorbid disease is essential for risk reduction in these patients [7,9]. The most common causes of death in our study included cardiac and infectious diseases, which is consistent with the current literature [16,17,18,19]. In addition, metabolic/endocrine disorders and vascular diseases were also a significant cause of mortality in this study [20].…”
Section: Discussionsupporting
confidence: 88%
“…The presence of residual renal function, even at a low level, is associated with a lower mortality risk in hemodialysis patients [8], underlying the impact of kidney function on CV prognosis. Furthermore, the presence of CV disease worsens the short- and long-term prognosis of CKD [8] as shown in a recent large cohort study comprising 2,964 CKD patients, with a follow-up time of 2.76 years, where CV events were associated with a significant increase in the risk of ESRD and all-cause mortality before ESRD [9]. …”
Section: Introductionmentioning
confidence: 99%